A qualitative exploration of STI partner notification services delivery models among key stakeholders in rural southwestern Uganda - Chitneni, Pooja; Owembabazi, Moran; Kanini, Eunice; Kansiime, Rosemary; Muyindike, Winnie R.; Psaros, Christina; Haberer, Jessica E.; Matthews, Lynn T. (Frontiers in Reproductive Health, 2025)
BackgroundComprehensive STI care requires not only patient treatment but STI partner notification (PN) and evaluation to prevent ongoing STI transmission and reinfection. In rural, southwestern Uganda, we explored healthcare practitioners’ views on three STI PN models that focused on task-shifting to non-physician practitioners to inform the development of a novel STI PN services delivery system.MethodsFrom September to November 2023, we conducted individual in-depth interviews with 32 participants from 4 categories (8 participants from each category): patients with a self-reported history of having an STI in Uganda, healthcare workers (physicians, nurses, and community health workers), pharmacists, and healthcare administrators (Ministry of Health officials and regional referral hospital administrators). Interviews explored participants’ views on a nursing-based, pharmacy-based, and community-based STI PN models as well as healthcare system tools and needs to facilitate PN. We used inductive and deductive approaches to generate a codebook guided by the Consolidated Framework for Implementation Research in a thematic analysis.ResultsTen female and twenty-two male participants participated in individual in-depth interviews. The median age of the patient and healthcare practitioner participants was 32 and 34 years, respectively. We found that (1) the nursing model was overall supported as nurses (though with one participant noting dissatisfaction with nurses), (2) pharmacies are well-positioned to engage in STI PN as they are early points of contact for patients, incentivized monetarily by PN and patient-delivered partner medication, and have the potential to physically restructure to create private spaces and increase counseling training, (3) the community-based model should center on village health teams and focus on advocacy and education.ConclusionGiven the high STI incidence globally and in sub-Saharan Africa, exploring innovative STI care models that resonate with patients and healthcare practitioners will be important. Future work includes a Delphi method to refine these models for testing.